Academic Senate Minutes 2010-11-18 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 9/16 and 10/14 approved. President Report. Special Report: SSU Preserves. Revision to the Formal Dispute Resolution Policy – First Reading completed. Occasional Report: Senate Diversity Subcommittee. Special Report: Early Start Program, pt 2. Resolution on Faculty Governance Right to Approve Early Start Program at Sonoma State University approved. SSU Early Start proposal endorsed. APC Report. Statewide Senator Report. Associated Students Report.